Heavy metal and organic compound bioaccumulation in bronze whaler sharks (Carcharhinus brachyurus) along the coastline of South Africa - Adebowale, Adetola Q (Department of Biological Sciences, 2024)
Anthropogenic activities may release harmful contaminants into the environment which are subsequently ingested and gradually bioaccumulated up the food-web. As apex predators, sharks are prone to heavy metal and persistent organic pollution, being especially vulnerable to such exposure over long lifespans, making these species indicators of systemic pollution in marine ecosystems. As tons of shark meat is harvested annually for consumption, the risk of human exposure to these harmful bioaccumulated pollutants cannot be over-emphasized. In this study, we examined heavy metal and persistent organic pollutant concentrations in the muscle tissue of 41 bronze whaler sharks (Carcharhinus brachyurus) sampled along the southern and eastern regions of the South African coastline. The concentrations of 10 heavy metals (Al, As, Cd, Cr, Cu, Fe, Hg, Mn, Pb, and Zn) and 8 congeners of polychlorinated biphenyls (PCB 28, 52, 101, 118, 138, 153, 180, 194) were analysed with inductively coupled plasma optical emission (ICP-OES) and gas chromatography coupled with low resolution mass spectrometry (GC-LRMS), respectively. Average concentrations of mercury (2.53 ±0.44 mg/kg), arsenic (16.60 ±1.38 mg/kg) and chromium (0.31 ±0.07 mg/kg) exceeded the World Health Organisation and other internationally recognised regulatory maximum limits for human consumption, while lead (0.14 ±0.09 mg/kg) and zinc (13.70 ±1.74 mg/kg) was close to the permissible limit. Aluminium, cadmium, copper, iron, manganese, and zinc were well below these regulatory limits, including those set by the Department of Health in South Africa and all PCB congener concentrations were below detectable limits. There were no significant differences in heavy metal concentration between sexes, except for chromium which was significantly higher in male sharks. We found that heavy metal concentrations varied significantly with shark size and sampling region. Mercury, chromium, and iron concentrations correlated positively and significantly (Hg: r = 0.78; Cr: r = 0.60; Fe: r = 0.47) with shark size (i.e., total length and body weight) while manganese had a strong negative correlation (r = -0.42). Cadmium, chromium, iron, and mercury concentrations were significantly higher in both adult (>230 cm) and sub-adults (130–230 cm) than in juvenile sharks (<130 cm) while manganese and aluminium concentrations were significantly higher in juvenile sharks. Mercury, iron, cadmium, and chromium concentrations were significantly higher in sharks sampled on the eastern coast while aluminium and manganese were higher in sharks from the southern coast of South Africa. Significantly positive and negative correlations were also found between heavy metals, suggesting underlying and systemic interactions between these pollutants. Our results underscore the ecological threat of heavy metal pollution along the South African coastline and the potential toxicity of consuming such shark meat from small-scale fisheries (i.e., high levels of mercury, arsenic and chromium toxicity have lethal effects). Potential sources of these heavy metal and organic pollutants include improper sewage treatment, dysfunctional waste-water treatment plants, and mining activities both inland and along South African coastline. Building on these study findings alongside existing literature and international policy, we suggest several recommendations to reduce such pollution and promote shark health and conservation in South Africa. Furthermore, detailed guidelines on safe shark meat consumption and more stringent environmental policies around waste-water management should be considered by the Departments of Health and Forestry, Fisheries, and the Environment in South Africa.